2007
DOI: 10.4269/ajtmh.2007.77.925
|View full text |Cite
|
Sign up to set email alerts
|

Relative Susceptibilties of South Texas Mosquitoes to Infection with West Nile Virus

Abstract: Three species of mosquitoes (Culex pipiens quinquefasciatus, Aedes aegypti, and Ae. albopictus) collected in Texas were compared with respect to their relative susceptibility to infection with West Nile virus (WNV) strain 114. Oral infection and dissemination rates were 73% infected with 86% dissemination for Ae. aegypti, 13% infected with 100% dissemination for Ae. albopictus, and 100% infected and disseminated for Cx. p. quinquefasciatus. The oral infectious dose required to establish a 50% infection rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
2
26
1
Order By: Relevance
“…Compared to intrathoracic inoculation (Table 1), the infection, disseminated infection and transmission rates were substantially lower in ϪWol mosquitoes (Table 2), which confirms that A. aegypti has a very poor vector competency for WNV (22)(23)(24) and that the gut provides a strong barrier against WNV infection. In ϩWol mosquitoes, the infection, disseminated infection and transmission rates were all negligible ( Table 2).…”
Section: Wolbachia Infection Induces Expression Of Gata4 In Mosquito supporting
confidence: 49%
See 2 more Smart Citations
“…Compared to intrathoracic inoculation (Table 1), the infection, disseminated infection and transmission rates were substantially lower in ϪWol mosquitoes (Table 2), which confirms that A. aegypti has a very poor vector competency for WNV (22)(23)(24) and that the gut provides a strong barrier against WNV infection. In ϩWol mosquitoes, the infection, disseminated infection and transmission rates were all negligible ( Table 2).…”
Section: Wolbachia Infection Induces Expression Of Gata4 In Mosquito supporting
confidence: 49%
“…A. aegypti is not considered the primary vector of WNVs, but the virus has the potential to infect and be disseminated by this mosquito (22)(23)(24). Infection and dissemination rates of up to 86%, respectively, were reported for A. aegypti infected with WNV (24). In our study, we found very low infection rates of A. aegypti (15%) when mosquitoes free of Wolbachia were orally fed with WNV, and this rate was nil in Wolbachia-infected mosquitoes.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…28,30 Infection rates of up to 100% have been observed (Florida and Texas), and high WNV transmission rates of up to 52% (southern California), calculated as a proportion of the number of mosquitoes tested. 30,[32][33][34][35] There are noticeable influences on mosquito susceptibility to WNV infection including extrinsic (e.g., initial viral dose, temperature, and length of incubation) and intrinsic (e.g., genetic strain, midgut physiology) factors. 32,[36][37][38] Generally, longer incubation periods, higher viral doses, and higher temperatures are expected to yield higher rates of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Culex mosquitoes are accepted as the primary global transmission vector (Hamer et al, 2008;Reisen et al, 2006;Vitek et al, 2008). There are reports of WNV transmission by Aedes mosquitoes, though they are not considered a primary vector in nature (Cupp et al, 2007;Farajollahi and Nelder, 2009;Vanlandingham et al, 2007). In India,Cx.…”
Section: Wnv Epidemiologymentioning
confidence: 99%